Nomograms for Fetal Cardiac Ventricular Width and Right‐to‐Left Ventricular Ratio. (7th October 2015) - Gabbay-Benziv, Rinat; Turan, Ozhan M.; Harman, Chris; Turan, Sifa
Abstract : Objectives: To establish nomograms for right ventricular (RV) and left ventricular (LV) widths and their ratio from 16 to 38 gestational weeks. Methods: We conducted a retrospective evaluation of 1242 fetal echocardiographic examinations with normal findings in a single referral medical center between 2007 and 2013. We excluded all echocardiographic examinations with abnormal findings. The RV and LV widths, measured in end diastole from inner to inner line below the valves' insertion at the 4‐chamber view, were obtained. Nomograms for the RV and LV widths and RV/LV ratio from 16 to 38 gestational weeks were constructed by using separate best‐fitted regression models for estimation of mean and standard deviation at each gestational age (GA). Results: Regression models for the RV and LV widths and RV/LV ratio were best fit by different‐degree polynomial regression. The mean RV and LV widths and RV/LV ratio (±2 SD) increased statistically with GA from 16 to 38 weeks: 4.13 (3.00–5.44) to 16.68 (12.98–20.83) mm, 4.21 (3.18–5.49) to 15.17 (11.60–19.56) mm, and 1.03 (0.87–1.23) to 1.06 (0.87–1.30), respectively. Although the width increments in the RV and LV were both statistically and clinically significant, the ratio increment seemed to fall into the error of measurement and thus has no clinical significance. Conclusions: Reference values for cardiac ventricle widths and their ratio throughout gestation were established. The RV/LV ratio increases with GA, although without clinical significance. These reference values will be useful in objective assessment of RV‐to‐LV disproportion.